Analisis Gaya Bahasa Pada Novel Thirteen Reasons Why Karya Jay Asher - Dewi Mutiara Indah Ayu; Herlina Lindaria Simanjuntak (Pusat riset dan Inovasi Nasional, 2025)
The purpose of this study is to determine the style of language used by Jay Asher in Thirteen Reasons Why and to find the dominant type of language style in Jay Asher's Thirteen Reasons Why. The research method used is qualitative. The results of this study are based on the theory of language style according to Keraf. The style of language that is widely used in this novel is of the 25 styles of language found, there are as many as 16 data (64%) are personification language styles, 5 data (20%) are ironic language styles, 2 data (8%) are figurative language Antiphrasis, 1 data (4%) is an allusion style, and 1 data (4%) is a metaphor style. Personification style is in the first place and is the dominant style of language used in Jay Asher's novel Thirteen Reasons Why.